ASP.NET core Razor Pages in action - Brind, Mike (Manning Publications Co., 2023)
ASP.NET Core Razor Pages in Action teaches you to develop dynamic websites using the powerful Razor Pages framework, .NET 6, and ASP.NET. Razor Pages generates HTML on the server, and is the perfect choice for eCommerce sites, intranet services, content management systems, and other apps that require reliability. In this book, you'll use Razor Pages to build a complete application for booking city breaks, learning to iterate amazing new features chapter-by-chapter. You'll even learn how to enhance your web applications with the huge ecosystem of C# libraries, and how to locate the perfect tool for your task using centralized repositories.